Implementation Strategy of Bringing Smart Mobility into Reality - Kristina Setyowati; Herwan Parwiyanto; Retno Suryawati (Universitas Sebelas Maret, 2021)
High urban vehicle growth rate results in high traffic jam rate and makes the portrait of urban transportation dull. It is a challenge and an opportunity all at once to provide smart mobility system. Smart mobility is a mobility system enabling the arrival at destination through less mobility, move freely, and less travel time. This study aims to find out the implementation strategy in bringing Smart Mobility into Reality. The strategies used were firstly, diversification strategy, the synchronization and cooperation with Central and Provincial governments. Secondly, it is aggressive strategy involving the strategy of applying E-Gov through IT Development, strategy of reinforcing the integration between Transportation modes and strategy of developing Office Strategy Plan referring to Master plan of Smart City. The method employed was qualitative one. Techniques of collecting data used were FGD and data documentation, while data analysis was carried out using A Procedure for Data Analysis. The result of research showed that there is a diversification strategy including providing smart public transportation (BST and feeder) and agglomeration transportation (TransJateng). Meanwhile, aggressive strategy includes 1) the strategy of intensifying the application of e-Gov through and developing IT of public transportation in “buy the service” scheme using TEMAN bus application, 2) strategy of reinforcing integration between Transportation modes in the form of improving accessibility of public transportation (BST) with feeder and agglomeration transportation (TransJateng), and 3) improving smart mobility by improving service quality and accessibility of public transportation.